Virological response to entecavir is associated with a better clinical outcome in chronic hepatitis B patients with cirrhosis. Issue 5 (5th April 2012) - Zoutendijk, Roeland; Reijnders, Jurrien GP; Zoulim, Fabien; Brown, Ashley; Mutimer, David J; Deterding, Katja; Hofmann, Wolf Peter; Petersen, Joerg; Fasano, Massimo; Buti, Maria; Berg, Thomas; Hansen, Bettina E; et al.
Abstract : Objective: Entecavir (ETV) is a potent inhibitor of viral replication in chronic hepatitis B and prolonged treatment may result in regression of fibrosis. The aim of this study was to investigate the effect of ETV on disease progression. Design: In a multicentre cohort study, 372 ETV-treated patients were investigated. Clinical events were defined as development of hepatocellular carcinoma (HCC), hepatic decompensation or death. Virological response (VR) was defined as HBV DNA <80 IU/ml. Results: Patients were classified as having chronic hepatitis B without cirrhosis (n=274), compensated cirrhosis (n=89) and decompensated cirrhosis (n=9). The probability of VR was not influenced by severity of liver disease (p=0.62). During a median follow-up of 20 months (IQR 11–32), the probability of developing clinical events was higher for patients with cirrhosis (HR 15.41 (95% CI 3.42 to 69.54), p<0.001). VR was associated with a lower probability of disease progression (HR 0.29 (95% CI 0.08 to 1.00), p=0.05) which remained after correction for established risk factors such as age. The benefit of VR was only significant in patients with cirrhosis (HR 0.22 (95% CI 0.05 to 0.99), p=0.04) and remained after excluding decompensated patients (HR 0.15 (95% CI 0.03 to 0.81), p=0.03). A higher HBV DNA threshold of 2000 IU/ml was not associated with the probability of disease progression (HR 0.20 (95% CI 0.03 to 1.10), p=0.10). Conclusion: VR to ETV is associated with a lower probability of disease progression in patients with cirrhosis, even after correction for possible baseline confounders. When using a threshold of 2000 IU/ml, the association between viral replication and disease progression was reduced, suggesting that complete viral suppression is essential for nucleoside/nucleotide analogue treatment, especially in patients with cirrhosis.